1996
DOI: 10.1039/cc9960002295
|View full text |Cite
|
Sign up to set email alerts
|

Molecular recognition-controlled membrane disruption by a bis(crown ether) bola-amphiphile

Abstract: Release of liposome-entrapped carboxyfluorescein is switched 'on' via molecular recognition of barium ion by a bis(crown ether carboxylate) bola-amphiphiie.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0
2

Year Published

1999
1999
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 6 publications
0
8
0
2
Order By: Relevance
“…Fyles and Zeng have reported that the release of liposome entrapped carboxyfluorescein is switched 'on' via molecular recognition of barium ions by a bis(crown ether carboxylate) bola-amphiphile 2. 58 Barboiu et al have Fig. 2 prepared a series of supramolecular complexes of the ammonium salt of a crown ether with different natural and non-natural amino acids (e.g.…”
Section: Crown Ethersmentioning
confidence: 99%
“…Fyles and Zeng have reported that the release of liposome entrapped carboxyfluorescein is switched 'on' via molecular recognition of barium ions by a bis(crown ether carboxylate) bola-amphiphile 2. 58 Barboiu et al have Fig. 2 prepared a series of supramolecular complexes of the ammonium salt of a crown ether with different natural and non-natural amino acids (e.g.…”
Section: Crown Ethersmentioning
confidence: 99%
“…Die Kristallstrukturen der entsprechenden Phasen A 4 Sn 9 und A 12 Sn 17 (A Alkalimetall) konnten bisher aufgrund schlechter Kristallqualität nicht aufgeklärt werden. [6] Obwohl in Lösung neunatomige Cluster schon vor über 100 Jahren beobachtet wurden [8] und ein derartiges Anion bereits 1976 erstmals strukturell charakterisiert wurde, [9] gelang die Isolierung von wohldefinierten Produkten aus Lösung nur in kleinen Mengen. Im Rahmen unserer Untersuchungen über lösliche homoatomare Zintl-Ionen [10] berichten wir im folgenden über einen neuen, sehr einfachen und effizienten Zugang zu homoatomaren Polyanionen aus den Elementen bei niedrigen Temperaturen.…”
Section: Thomas F Fässler* Und Rudolf Hoffmannunclassified
“…The crystal structure of the corresponding phase A 4 Sn 9 or A 12 Sn 17 (A alkali metal) could not be elucidated due to poor crystal quality. [6] Though nine-atom clusters were observed in solution over 100 years ago [8] and the first structural characterization was carried out already in 1976, [9] only small amounts of well-defined products could be isolated from solution. In the course of our studies of soluble, homoatomic Zintl ions, [10] we report here a novel, very simple and efficient access to homoatomic polyanions from the elements at low temperatures.…”
mentioning
confidence: 99%
“…[5,6] We selected (2E,7E)-9-chloronona-2,7-dienyl carbamate (6) [7] as substrate in order to compensate for the unfavorable equilibrium state of the cyclization with an irreversible elimination step. [8] Compound 6 was obtained from pentanedial (1) by standard methods (Scheme 2). Treatment of 6 (E:Z 98:2)…”
mentioning
confidence: 99%